2021
DOI: 10.3390/ijms22179402
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomic Analysis of Tolerant and Sensitive Varieties Reveals That Phenylpropanoid Biosynthesis Contributes to Salt Tolerance in Mulberry

Abstract: Mulberry, an important woody tree, has strong tolerance to environmental stresses, including salinity, drought, and heavy metal stress. However, the current research on mulberry resistance focuses mainly on the selection of resistant resources and the determination of physiological indicators. In order to clarify the molecular mechanism of salt tolerance in mulberry, the physiological changes and proteomic profiles were comprehensively analyzed in salt-tolerant (Jisang3) and salt-sensitive (Guisangyou12) mulbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…Glutathione S-transferase were induced in GZ and degraded in HN in our study. Previous research indicated that overexpression of the glutathione S-transferase could enhanced salt resistance of mulberry ( Gan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Glutathione S-transferase were induced in GZ and degraded in HN in our study. Previous research indicated that overexpression of the glutathione S-transferase could enhanced salt resistance of mulberry ( Gan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…But those studies were mainly focused on Arabidopsis thaliana , Nicotiana tabacum , Oryza sativa , and other model plants (Dani et al 2005; Jiang et al 2007; Lakra et al 2019; Manaa et al 2011; Ndimba et al 2005; Sobhanian et al 2010; Zörb et al 2010), and some halophytic species, such as Suaeda salsa , Mesembryanthemum crystallinum , Haloxylon salicornicum , Puccinellia tenuiflora , and Porteresia coarctata (Barkla et al 2009; Li et al 2011; Panda et al 2020; Sengupta & Majumder 2009; Yu et al 2011). Proteomics approach has also been exploited to identify the key salt‐tolerance proteins by comparing the related plant species or contrasting genotypes under salinity, such as Arabidopsis thaliana/Thellungiella halophila , Triticum aestivum/Thinopyrum ponticum , Oryza sativa , Hordeum vulgare , Zea mays , and recently in Morus alba (Chen et al 2019; Damaris et al 2016; Gan et al 2021; Hussain et al 2019; Lakra et al 2018, 2019; Luo et al 2018; Pang et al 2010; Wang et al 2008; Witzel et al 2010). However, in case of millets, only a single study reported salt‐specific proteome responses, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In the cross-talk between different signaling networks, various salt-stress proteins regulate osmoregulation and ion transport and compartmentalize toxic ions in the vacuole. Such activities require the coordinated activity of vesicles and proteins trafficking in different cellular organelles (Nam et al, 2012;Wang et al, 2015b;Zhao et al, 2018;Gan et al, 2021). Thus, plants likely express specific proteins to perform particular functions (Figure 1).…”
Section: How Stress Proteins Enable Plants To Resist Salt Stressmentioning
confidence: 99%